Reasoning the Disaster - Simmons, Laurance (Filozofski vestnik, 2017)
How do we think the disaster? Think towards or against the coming disaster? Natural disaster, industrial and technological disaster, moral disaster, and now economic and financial disaster. This paper starts from the issue of our relationship with catastrophes that have not yet happened and it is based on the work of cultural theorist Slavoj Žižek and French philosopher Jean-Pierre Dupuy. The essence of catastrophe has become normal for what Žižek calls our Western administered world – we now govern according to scenarios of war, terror, ecological disasters etc; the normal run of our societies is continually threatened by these things. However, since he insists that catastrophe involves the notion of “luck” can it be reasoned? It would appear not because we can only answer when we learn the outcome of some event. So are we justified in taking preventative action against global warming? If we do the catastrophe might not occur? But can we be sure that it would have anyway? And if we don’t take action will it occur? We know that the catastrophe is possible, probable even, yet we do not believe it will really happen. Can we make a rational choice before the apocalypse? If we are to confront the threat of a catastrophe Dupuy believes we need to break out of a historical, linear notion of time. The new notion of time (what Dupuy calls “the time of a project’) is not a line between past and future; it is a closed circuit. The future is casually produced by our actions in the past but the way we act is determined by how we anticipate the future, and how we react to this anticipation. As he thinks through the relationship between the crisis of the sacred and our inability to imagine and avoid a catastrophic future, Dupuy develops the idea of an enlightened catastrophism as an alternative to the principle of reasoned precaution.